Bacillus coagulans (PROBACI) in treating constipation-dominant functional bowel disorders. Issue 19 (May 2020) - Chang, Chen-Wang; Chen, Ming-Jen; Shih, Shou-Chuan; Chang, Ching-Wei; Chiau, Jen-Shiu Chiang; Lee, Hung-Chang; Lin, Yang-Sheng; Lin, Wei-Chen; Wang, Horng-Yuan
Abstract : Abstract: Bacillus coagulans (PROBACI) bacteria have been examined for efficacy against infectious or inflammatory bowel diseases. The aim of this observational and cross-sectional study was to evaluate the effects of PROBACI against various functional bowel symptoms. Thirty-eight enrolled patients (36.5 ± 12.6 years) with functional bowel disorders in a gastrointestinal clinic were administered PROBACI (300-mg formulation containing 1 × 10 9 colony-forming units of B coagulans ) twice/day over a 4-week period. Abdominal pain, abdominal distention, and global assessment were evaluated using a 5-point visual analog scale. The defecation characteristics, discomfort level, and effort required for defecation were recorded. The gut-microbiota composition in terms of the Firmicutes/Bacteroidetes ratio was analyzed by 16S-ribosomal RNA gene sequencing with stool samples at days 0, 14, and 28 post-treatment. The 38 patients achieved significant improvements in abdominal pain (2.8 ± 0.5 to 3.3 ± 0.7, P = .0009), abdominal distention (2.5 ± 0.7 to 3.2 ± 0.8, P = .0002), and global assessment (2.7 ± 0.6 to 3.6 ± 0.7, P = .0001) from days 0 to 14. Compared with the diarrhea group, the constipation group achieved greater improvements in terms of discomfort during defecation (2.5 ± 0.7 to 3.1 ± 0.7, P = .02) and normalization of defecation style (50% vs 7.1%, P = .007) by day 28. A difference was observed in the Firmicutes/Bacteroidetes ratio between the constipation-dominant group (118.0) and diarrhea-dominant group (319.2), but this difference was not significant. PROBACI provided control of abdominal pain, less discomfort during defecation, and a more normalized defecation style, especially in the constipation-dominant group.